Activation of Rho-kinase and focal adhesion kinase regulates the organization of stress fibers and focal adhesions in the central part of fibroblasts - Kazuo Katoh (PeerJ, 2017)
Specific regulation and activation of focal adhesion kinase (FAK) are thought to be important for focal adhesion formation, and activation of Rho-kinase has been suggested to play a role in determining the effects of FAK on the formation of stress fibers and focal adhesions. To clarify the role of FAK in stress fiber formation and focal adhesion organization, the author examined the formation of new stress fibers and focal adhesions by activation of Rho-kinase in FAK knockout (FAK–/–) fibroblasts. FAK–/– cells were elliptical in shape, and showed reduced numbers of stress fibers and focal adhesions in the central part of the cells along with large focal adhesions in the peripheral regions. Activation of Rho-kinase in FAK–/– cells transiently increased the actin filaments in the cell center, but these did not form typical thick stress fibers. Moreover, only plaque-like structures as the origins of newly formed focal adhesions were observed in the center of the cell. Furthermore, introduction of an exogenous GFP-labeled FAK gene into FAK–/– cells resulted in increased numbers of stress fibers and focal adhesions in the center of the cells, which showed typical fibroblast morphology. These results indicated that FAK plays an important role in the formation of stress fibers and focal adhesions as well as in regulation of cell shape and morphology with the activation of Rho-kinase.